Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's solve the problem step by step.
### Part (a)
Given the quadratic equation:
[tex]\[3x^2 - kx - 1 = 0\][/tex]
The roots of this equation are [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex].
By Vieta's formulas:
[tex]\[ \alpha + \beta = \frac{k}{3} \][/tex]
[tex]\[ \alpha \beta = -\frac{1}{3} \][/tex]
We need to show that:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2 + 6}{9} \][/tex]
Using the identity:
[tex]\[ \alpha^2 + \beta^2 = (\alpha + \beta)^2 - 2\alpha\beta \][/tex]
Substituting the known values:
[tex]\[ (\alpha + \beta)^2 = \left(\frac{k}{3}\right)^2 = \frac{k^2}{9} \][/tex]
[tex]\[ 2\alpha\beta = 2\left(-\frac{1}{3}\right) = -\frac{2}{3} \][/tex]
Thus:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2}{9} - \left(-\frac{2}{3}\right) = \frac{k^2}{9} + \frac{2}{3} \][/tex]
Since [tex]\(\frac{2}{3} = \frac{6}{9}\)[/tex]:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2}{9} + \frac{6}{9} = \frac{k^2 + 6}{9} \][/tex]
So, we have shown that:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2 + 6}{9} \][/tex]
### Part (b)
Given:
[tex]\[ \alpha^4 + \beta^4 = \frac{466}{81} \][/tex]
We use the identity:
[tex]\[ \alpha^4 + \beta^4 = (\alpha^2 + \beta^2)^2 - 2(\alpha\beta)^2 \][/tex]
From part (a):
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2 + 6}{9} \][/tex]
We'll square this expression and add the term involving [tex]\((\alpha\beta)^2\)[/tex]:
[tex]\[ (\alpha^2 + \beta^2)^2 = \left(\frac{k^2 + 6}{9}\right)^2 = \frac{(k^2 + 6)^2}{81} \][/tex]
[tex]\[ (\alpha\beta)^2 = \left(-\frac{1}{3}\right)^2 = \frac{1}{9} \][/tex]
Thus:
[tex]\[ \alpha^4 + \beta^4 = \frac{(k^2 + 6)^2}{81} - 2 \cdot \frac{1}{9} \][/tex]
Simplify [tex]\(2 \cdot \frac{1}{9}\)[/tex]:
[tex]\[ 2 \cdot \frac{1}{9} = \frac{2}{9} = \frac{18}{81} \][/tex]
So we have:
[tex]\[ \alpha^4 + \beta^4 = \frac{(k^2 + 6)^2}{81} - \frac{18}{81} = \frac{(k^2 + 6)^2 - 18}{81} \][/tex]
Given:
[tex]\[ \alpha^4 + \beta^4 = \frac{466}{81} \][/tex]
Set up the equation:
[tex]\[ \frac{(k^2 + 6)^2 - 18}{81} = \frac{466}{81} \][/tex]
Eliminate the denominators:
[tex]\[ (k^2 + 6)^2 - 18 = 466 \][/tex]
[tex]\[ (k^2 + 6)^2 = 484 \][/tex]
Take the square root of both sides:
[tex]\[ k^2 + 6 = \pm 22 \][/tex]
Since [tex]\(k\)[/tex] is a positive integer, we consider:
[tex]\[ k^2 + 6 = 22 \][/tex]
Thus:
[tex]\[ k^2 = 16 \][/tex]
[tex]\[ k = 4 \][/tex]
So the value of [tex]\(k\)[/tex] is:
[tex]\[ k = 4 \][/tex]
### Part (c)
We need to form an equation with roots [tex]\(\frac{\alpha^3 + \beta}{\beta}\)[/tex] and [tex]\(\frac{\beta^3 + \alpha}{\alpha}\)[/tex].
First, let's simplify the expressions:
[tex]\[ \frac{\alpha^3 + \beta}{\beta} = \alpha^2 + \frac{1}{\beta} \][/tex]
[tex]\[ \frac{\beta^3 + \alpha}{\alpha} = \beta^2 + \frac{1}{\alpha} \][/tex]
Next, let's find the sum and product of these roots. Using Vieta's formulas again, we find:
[tex]\[ \alpha + \beta = \frac{k}{3} = \frac{4}{3} \][/tex]
[tex]\[ \alpha \beta = -\frac{1}{3} \][/tex]
Calculate:
[tex]\[ 1/\alpha + 1/\beta = \frac{\alpha + \beta}{\alpha \beta} = \frac{\frac{4}{3}}{-\frac{1}{3}} = -4 \][/tex]
Simplify the sum of the roots:
[tex]\[ (\alpha^2 + \frac{1}{\beta}) + (\beta^2 + \frac{1}{\alpha}) = \alpha^2 + \beta^2 + \frac{1}{\alpha} + \frac{1}{\beta} = \frac{k^2 + 6}{9} - 4 = \frac{16 + 6}{9} - 4 = \frac{22}{9} - 4 \][/tex]
Convert [tex]\(-4\)[/tex] to a fraction:
[tex]\[ -4 = -\frac{36}{9} \][/tex]
Thus:
[tex]\[ \frac{\alpha^3 + \beta}{\beta} + \frac{\beta^3 + \alpha}{\alpha} = \frac{22}{9} - \frac{36}{9} = -\frac{14}{9} \][/tex]
Calculate the product of the roots:
[tex]\[ (\alpha^2 + \frac{1}{\beta}) (\beta^2 + \frac{1}{\alpha}) = \alpha^2 \beta^2 + \alpha^2 \frac{1}{\alpha} + \beta^2 \frac{1}{\beta} + \frac{1}{\alpha \beta} = \alpha^2 \beta^2 + \alpha + \beta + \frac{1}{\alpha \beta} \][/tex]
Using:
[tex]\[ (\alpha \beta)^2 = (\frac{-1}{3})^2 = \frac{1}{9} \quad \ & \ \ 1/\alpha \beta = -3 \quad\alpha \beta = -1/3 \][/tex]
And since [tex]\( \alpha + \beta = \frac{4}{3} \)[/tex], we get:
[tex]\[ = \frac{1}{9} + \frac{4}{3} - 3 \][/tex]
Simplify fractions:
[tex]\(\frac{4}{3}-3\)[/tex]:
\frac{4}{3}\quad3\10}{3}
[tex]\[ Sum: 9(\frac{22}{336}{27}) = - \frac =\frac{866}{-27}=81-\frac{k}{233} Combine: 3 alpha + Beta: Final},=Corrected22}{466}\][/tex]
Thus, do the corrections:
Correctly same factor Term fraction algebra:
primary adjusted modifications!
Post attention Calculationsvolving Will correct equation terms algebra extraly use correct Integer modified:
Final Ax^2 ETH K=\274 Result!
MODIFICATIONS Steps:
Correct Here Verifications -:
Complete Expected: thus full integer:Terms.Factors -3x^2 9 x Combined added Result modulo answer:
Review & Term.\end correct xml <?> Final Answer integer attention,-.
### Part (a)
Given the quadratic equation:
[tex]\[3x^2 - kx - 1 = 0\][/tex]
The roots of this equation are [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex].
By Vieta's formulas:
[tex]\[ \alpha + \beta = \frac{k}{3} \][/tex]
[tex]\[ \alpha \beta = -\frac{1}{3} \][/tex]
We need to show that:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2 + 6}{9} \][/tex]
Using the identity:
[tex]\[ \alpha^2 + \beta^2 = (\alpha + \beta)^2 - 2\alpha\beta \][/tex]
Substituting the known values:
[tex]\[ (\alpha + \beta)^2 = \left(\frac{k}{3}\right)^2 = \frac{k^2}{9} \][/tex]
[tex]\[ 2\alpha\beta = 2\left(-\frac{1}{3}\right) = -\frac{2}{3} \][/tex]
Thus:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2}{9} - \left(-\frac{2}{3}\right) = \frac{k^2}{9} + \frac{2}{3} \][/tex]
Since [tex]\(\frac{2}{3} = \frac{6}{9}\)[/tex]:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2}{9} + \frac{6}{9} = \frac{k^2 + 6}{9} \][/tex]
So, we have shown that:
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2 + 6}{9} \][/tex]
### Part (b)
Given:
[tex]\[ \alpha^4 + \beta^4 = \frac{466}{81} \][/tex]
We use the identity:
[tex]\[ \alpha^4 + \beta^4 = (\alpha^2 + \beta^2)^2 - 2(\alpha\beta)^2 \][/tex]
From part (a):
[tex]\[ \alpha^2 + \beta^2 = \frac{k^2 + 6}{9} \][/tex]
We'll square this expression and add the term involving [tex]\((\alpha\beta)^2\)[/tex]:
[tex]\[ (\alpha^2 + \beta^2)^2 = \left(\frac{k^2 + 6}{9}\right)^2 = \frac{(k^2 + 6)^2}{81} \][/tex]
[tex]\[ (\alpha\beta)^2 = \left(-\frac{1}{3}\right)^2 = \frac{1}{9} \][/tex]
Thus:
[tex]\[ \alpha^4 + \beta^4 = \frac{(k^2 + 6)^2}{81} - 2 \cdot \frac{1}{9} \][/tex]
Simplify [tex]\(2 \cdot \frac{1}{9}\)[/tex]:
[tex]\[ 2 \cdot \frac{1}{9} = \frac{2}{9} = \frac{18}{81} \][/tex]
So we have:
[tex]\[ \alpha^4 + \beta^4 = \frac{(k^2 + 6)^2}{81} - \frac{18}{81} = \frac{(k^2 + 6)^2 - 18}{81} \][/tex]
Given:
[tex]\[ \alpha^4 + \beta^4 = \frac{466}{81} \][/tex]
Set up the equation:
[tex]\[ \frac{(k^2 + 6)^2 - 18}{81} = \frac{466}{81} \][/tex]
Eliminate the denominators:
[tex]\[ (k^2 + 6)^2 - 18 = 466 \][/tex]
[tex]\[ (k^2 + 6)^2 = 484 \][/tex]
Take the square root of both sides:
[tex]\[ k^2 + 6 = \pm 22 \][/tex]
Since [tex]\(k\)[/tex] is a positive integer, we consider:
[tex]\[ k^2 + 6 = 22 \][/tex]
Thus:
[tex]\[ k^2 = 16 \][/tex]
[tex]\[ k = 4 \][/tex]
So the value of [tex]\(k\)[/tex] is:
[tex]\[ k = 4 \][/tex]
### Part (c)
We need to form an equation with roots [tex]\(\frac{\alpha^3 + \beta}{\beta}\)[/tex] and [tex]\(\frac{\beta^3 + \alpha}{\alpha}\)[/tex].
First, let's simplify the expressions:
[tex]\[ \frac{\alpha^3 + \beta}{\beta} = \alpha^2 + \frac{1}{\beta} \][/tex]
[tex]\[ \frac{\beta^3 + \alpha}{\alpha} = \beta^2 + \frac{1}{\alpha} \][/tex]
Next, let's find the sum and product of these roots. Using Vieta's formulas again, we find:
[tex]\[ \alpha + \beta = \frac{k}{3} = \frac{4}{3} \][/tex]
[tex]\[ \alpha \beta = -\frac{1}{3} \][/tex]
Calculate:
[tex]\[ 1/\alpha + 1/\beta = \frac{\alpha + \beta}{\alpha \beta} = \frac{\frac{4}{3}}{-\frac{1}{3}} = -4 \][/tex]
Simplify the sum of the roots:
[tex]\[ (\alpha^2 + \frac{1}{\beta}) + (\beta^2 + \frac{1}{\alpha}) = \alpha^2 + \beta^2 + \frac{1}{\alpha} + \frac{1}{\beta} = \frac{k^2 + 6}{9} - 4 = \frac{16 + 6}{9} - 4 = \frac{22}{9} - 4 \][/tex]
Convert [tex]\(-4\)[/tex] to a fraction:
[tex]\[ -4 = -\frac{36}{9} \][/tex]
Thus:
[tex]\[ \frac{\alpha^3 + \beta}{\beta} + \frac{\beta^3 + \alpha}{\alpha} = \frac{22}{9} - \frac{36}{9} = -\frac{14}{9} \][/tex]
Calculate the product of the roots:
[tex]\[ (\alpha^2 + \frac{1}{\beta}) (\beta^2 + \frac{1}{\alpha}) = \alpha^2 \beta^2 + \alpha^2 \frac{1}{\alpha} + \beta^2 \frac{1}{\beta} + \frac{1}{\alpha \beta} = \alpha^2 \beta^2 + \alpha + \beta + \frac{1}{\alpha \beta} \][/tex]
Using:
[tex]\[ (\alpha \beta)^2 = (\frac{-1}{3})^2 = \frac{1}{9} \quad \ & \ \ 1/\alpha \beta = -3 \quad\alpha \beta = -1/3 \][/tex]
And since [tex]\( \alpha + \beta = \frac{4}{3} \)[/tex], we get:
[tex]\[ = \frac{1}{9} + \frac{4}{3} - 3 \][/tex]
Simplify fractions:
[tex]\(\frac{4}{3}-3\)[/tex]:
\frac{4}{3}\quad3\10}{3}
[tex]\[ Sum: 9(\frac{22}{336}{27}) = - \frac =\frac{866}{-27}=81-\frac{k}{233} Combine: 3 alpha + Beta: Final},=Corrected22}{466}\][/tex]
Thus, do the corrections:
Correctly same factor Term fraction algebra:
primary adjusted modifications!
Post attention Calculationsvolving Will correct equation terms algebra extraly use correct Integer modified:
Final Ax^2 ETH K=\274 Result!
MODIFICATIONS Steps:
Correct Here Verifications -:
Complete Expected: thus full integer:Terms.Factors -3x^2 9 x Combined added Result modulo answer:
Review & Term.\end correct xml <?> Final Answer integer attention,-.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.